Bringing football back to campus : a case study on campus expansion and community pushback - Cintron, Alicia M.; Wegner, Christine E. (London : SAGE Publications: SAGE Business Cases Originals, 2021)
Temple University long grappled with a home field disadvantage for its football program. The Owls football program, a member of the American Athletic Conference (AAC) in the National Collegiate Athletic Association (NCAA), has never played on its main campus, which is located in the heart of North Philadelphia, Pennsylvania. Temple has played at Lincoln Financial Field, home of the National Football League (NFL) Eagles, since the stadium opened in 2003. Temple's 15-year lease at Lincoln Financial Field was set to expire at the end of 2018. Given the impending lease expiration and potential increase in expenses, university officials prepared an initial proposal to develop a 25,000-seat on-campus football stadium as an alternative to Lincoln Financial Field. But the university needed to ensure the initial proposal plan considered relevant stakeholders as these groups were vital to the fabric and success of the university. The Board of Trustees wanted to make sure a community engagement campaign was employed and that the feedback collected would be implemented in the initial plans. This case asks students to consider the perspectives of multiple stakeholders in creating a community relations campaign to garner support for the new stadium.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Temple University -- Football -- Case studies; College sports -- Economic aspects -- Pennsylvania -- North Philadelphia -- Case studies; Football -- Pennsylvania -- North Philadelphia -- Case studies; College sports -- Pennsylvania -- North Philadelphia -- Management -- Case studies